2022
DOI: 10.1007/s40122-022-00438-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Manipulation Under Anesthesia for Secondary Frozen Shoulder: A Randomized Controlled Trial

Abstract: Introduction: Manipulation under anesthesia (MUA) is often used for frozen shoulder treatment, but controversy still exists regarding MUA compared with conservative treatment. This research was conducted to compare the outcome between MUA and celecoxib (CLX) in secondary frozen shoulder. Methods: Patients with secondary frozen shoulder were randomized into two groups, an MUA plus exercise (EX) group and a CLX plus EX group. Clinical outcomes were documented at baseline and at 1 day, 2, 4, and 12 weeks after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…From the results of evaluating muscle strength for 3 times of therapy every Tuesday and Friday from T1-T3 there was a minimal increase in abductor and adductor muscle strength in patients, this is in line with previous studies which explained that patients who had frozen shoulder had significant increases in muscle strength. which is a little due to the age conditions of patients who have stepped on to the elderly (Xu et al, 2022)…”
Section: Resultsmentioning
confidence: 99%
“…From the results of evaluating muscle strength for 3 times of therapy every Tuesday and Friday from T1-T3 there was a minimal increase in abductor and adductor muscle strength in patients, this is in line with previous studies which explained that patients who had frozen shoulder had significant increases in muscle strength. which is a little due to the age conditions of patients who have stepped on to the elderly (Xu et al, 2022)…”
Section: Resultsmentioning
confidence: 99%
“…8,11,12,13 A recent RCT compared the effects MUA and celecoxib for frozen shoulder concluded that MUA was superior than celecoxib in terms of pain control and passive ROM. 14 However, MUA is a less precise procedure, and authors have pointed out that it is not evident whether the manipulation is causing more damage than good. Moreover, other reported adverse effects include proximal humeral (shaft) fracture, glenoid rim fracture, and brachial plexus traction injury.…”
Section: Discussionmentioning
confidence: 99%